2008
DOI: 10.3748/wjg.14.800
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular epithelioid cell tumor of the liver coexisting with a gastrointestinal stromal tumor

Abstract: Approximately 10% of patients with gastrointestinal stromal tumors (GIST) develop other neoplasms, either synchronously or metachronously. In this report we describe coexistence of a gastrointestinal stromal tumor and a hepatic perivascular epithelioid cell tumor (PEComa) in a 51-year-old woman with no evidence of tuberous sclerosis. A subcapsular hepatic nodule (0.8 cm in diameter) was found during surgery for symptomatic gastric neoplasm (15 cm in diameter) arising from the lesser curvature. Both tumors reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…9 Mesenchymal neoplasms of the liver are very uncommon. 10 A review of the pertinent literature revealed only a few cases of PEComa of the liver; [11][12][13][14][15][16][17] most of them were referred to as angiomyolipoma. The authors herein present a case report of extremely rare histological tumor type of the liver, namely primary clear cell "sugar" tumor with myomelanocytic differentiation, and demonstrate its clinical, imaging, pathological, and immunohistochemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…9 Mesenchymal neoplasms of the liver are very uncommon. 10 A review of the pertinent literature revealed only a few cases of PEComa of the liver; [11][12][13][14][15][16][17] most of them were referred to as angiomyolipoma. The authors herein present a case report of extremely rare histological tumor type of the liver, namely primary clear cell "sugar" tumor with myomelanocytic differentiation, and demonstrate its clinical, imaging, pathological, and immunohistochemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Carlos et al (8) reported a case of PEComa coexisting with GIST. Loss of heterozygosity (LOH) in chromosome 16p (harboring the TSC2 locus) has been detected in some PEComas, but it has not been investigated in GISTs (1, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Four patients had normal levels of serum AFP and were negative for hepatitis B surface antigen and anti-hepatitis C virus antigen (6,10,12,15); reports of the other 8 cases did not mention this. Two patients had a history of melanoma (13,14), and 1 had a history of GIST (8). Four had no history of tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations